The Relationship between Organizational Management and Nurse Job Satisfaction - Rossa, M. Adila; Darmojo, Hardjito S; Siswosuharjo, Partono (LPPM AKPER FATMAWATI, 2023)
This study aims to analyze the effectiveness of Outcome-Based Education (OBE)-based nursing student competency measurement in improving the quality of clinical learning and the professional readiness of graduates. The research method used a quantitative approach with a descriptive-analytical design for nursing students who had participated in integrated clinical practice. The research instruments included competency assessment sheets, student perception questionnaires, and documentation of academic evaluation results. Data were statistically analyzed using descriptive and inferential tests to identify the relationship between OBE implementation and competency achievement levels. The results showed that systematic OBE implementation improved clinical abilities, therapeutic communication skills, and evidence-based nursing decision-making. Furthermore, students demonstrated high levels of learning satisfaction because the learning objectives, evaluation methods, and feedback were clearly structured and measurable. These findings confirm that curriculum integration, authentic assessment, and learning reflection are critical factors in the successful implementation of OBE. Therefore, strengthening the outcome-based competency evaluation system is necessary to ensure the quality of nursing education and the readiness of graduates to face the complex demands of healthcare